2016
DOI: 10.7186/bgsm62201609
|View full text |Cite
|
Sign up to set email alerts
|

Threats faced by groundwater: A preliminary study in Kuala Selangor

Abstract: Coastal ecosystems are particularly vulnerable to climate change as the rise in sea level will lead to damage of infrastructure, degradations of agricultural areas, contamination of surface and groundwater and loss of biodiversity; which covers a wide range of negative impacts to various socio-economic sectors. Preliminary findings indicate that Kuala Selangor, which hosts several groundwater aquifers and serves as a significant "rice bowl" for the nation is susceptible to groundwater salinization and other im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The groundwater salinization in Banting, Kuala Langat significantly showed that there has been an influence from seawater intrusion, based on the current finding. This is similar to Jamaluddin et al (2016) which revealed that there were threats of high salinity in groundwater affected by sea level rise in Kuala Langat. The findings from the hydrogeochemistry analysis in the current study revealed that the groundwater sources in Kuala Langat indicate the influence of seawater intrusion.…”
Section: Seawater Intrusion In Groundwatersupporting
confidence: 84%
“…The groundwater salinization in Banting, Kuala Langat significantly showed that there has been an influence from seawater intrusion, based on the current finding. This is similar to Jamaluddin et al (2016) which revealed that there were threats of high salinity in groundwater affected by sea level rise in Kuala Langat. The findings from the hydrogeochemistry analysis in the current study revealed that the groundwater sources in Kuala Langat indicate the influence of seawater intrusion.…”
Section: Seawater Intrusion In Groundwatersupporting
confidence: 84%
“…As Kuala Selangor consist of natural resources, it is more prone to the impact of sea level rise leading to the flooding of low-lying areas of the coastal zone. This is because, among the main causes of coastal inundation are sea level rise, erosion, wetland changes, saltwater contamination of surface and groundwater, and increase groundwater surface (McLeod et al, 2010;Nicholls, 2011;Brown et al, 2013;Wong et al, 2014;Jamaluddin et al, 2016;Mucerino et al, 2019;Hamid et al, 2019;Hamid et al, 2021).…”
Section: Evaluation Of the Potential Coastal Inundation At Pelabuhan ...mentioning
confidence: 99%